IMMIGRANTS’ EXPERIENCES OF BECOMING BILINGUAL (A Literature Review) - Sabarniati, Sabarniati; Fitriani, Naria (Jurnal Sains Riset, 2023)
An individual or immigrant with his experience of acquiring bilingual naturally confronts some obstacles. The process of developing the person’s bilingual has been in different phases. There were inquiries about the adult’s difficulties acquiring the target language. Relating to those issues, this study aims at examining experts’ perspectives on how immigrants acquire bilingualism. All documents including articles and researches correlating with this topic were collected. The chosen data were evaluated, in sighted, argued and drafted qualitatively. Regarding with this issue there are four topics discussed in detail; fossilization, native-like attainment, language maintenance and language threat. Among of them, fossilization plays an essential role for it as it concerns on adult’s bilingual.